LITERACY PLAYS AN IMPORTANT ROLE IN WOMEN EMPOWERMENT DEVELOPMENT (International Journal of Food and Nutritional Sciences, 2023)
India's primary occupation is agriculture and agriculture does not require much education, so the family is not inclined to teach. But if taught, only boys are taught more, girls are little neglected. Therefore, the overall development of girls, which is necessary, is less developed. Therefore, parents who are educated and who know the importance of literacy teach girls in primary form like boys and also guide them about their rights, duties and responsibilities and how to behave in various fields. Therefore, women who are well-educated benefit from education very well and women who are illiterate do not benefit accordingly, so this study shows the importance of literacy and how women can be empowered with the help of literacy. this study used SPSS software for chi-Squar test and correlation, gamma test .